2003
DOI: 10.1038/nm871
|View full text |Cite
|
Sign up to set email alerts
|

Targeting exogenous genes to tumor angiogenesis by transplantation of genetically modified hematopoietic stem cells

Abstract: Angiogenic tumor vessels are promising targets for the activity and the selective delivery of cancer therapeutics. The bone marrow contributes different cell types to the tumor stroma, including hematopoietic cells and, as recently suggested, vascular endothelial cells (ECs). Thus, transplantation of genetically modified bone marrow progenitors may represent a vehicle for the transport of gene therapy to tumors. We transduced bone marrow progenitors with lentiviral vectors expressing genes from transcription-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
480
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(518 citation statements)
references
References 24 publications
33
480
0
5
Order By: Relevance
“…These results suggest that Arf6 in endothelial cells plays a crucial role in tumour angiogenesis, thereby regulating tumour growth. Since Tie2 is expressed in haematopoietic as well as endothelial cells 28 and Tie2-expressing bone marrow-derived monocytes have been reported to promote tumour angiogenesis in mouse tumour models 29,30 , we examined the possibility that ablation of Arf6 in haematopoietic cells contributed to or created the tumour angiogenesis phenotype by performing bone marrow transplantations. Bone marrow reconstitution efficiency was assessed by determining the frequency of Ly5.1 Ć¾ haematopoietic cells in the Ly5.2-expressing recipient mice ( Supplementary Fig.…”
Section: Endothelial Arf6 Regulates Tumour Angiogenesis and Growthmentioning
confidence: 99%
“…These results suggest that Arf6 in endothelial cells plays a crucial role in tumour angiogenesis, thereby regulating tumour growth. Since Tie2 is expressed in haematopoietic as well as endothelial cells 28 and Tie2-expressing bone marrow-derived monocytes have been reported to promote tumour angiogenesis in mouse tumour models 29,30 , we examined the possibility that ablation of Arf6 in haematopoietic cells contributed to or created the tumour angiogenesis phenotype by performing bone marrow transplantations. Bone marrow reconstitution efficiency was assessed by determining the frequency of Ly5.1 Ć¾ haematopoietic cells in the Ly5.2-expressing recipient mice ( Supplementary Fig.…”
Section: Endothelial Arf6 Regulates Tumour Angiogenesis and Growthmentioning
confidence: 99%
“…22 In contrast to these studies, no contribution of bone marrow-derived cells to tumorigenesis was found by others. 23,24 Additional studies could not detect bone marrow-derived EPCs in the tumor vasculature but defined bone marrow-derived cells of hematopoietic origin that contributed indirectly to tumor neovascularization, 25,26 such as by generation of vascular mural cells. 26 These partially conflicting data suggest that while bone marrow-derived cells take part in the cellular makeup of tumor vessels, their relative contribution to tumor ECs, periendothelial cells and nonstructural but proangiogenic cells has yet to be determined.…”
Section: Epcs In Tumor Angiogenesismentioning
confidence: 99%
“…Transduction of EPCs and their putative precursors with retrovirus 16,63 and lentivirus 25 vectors is feasible. These vectors stably integrate into the genome, allowing for long-term transgene expression.…”
Section: Genetic Modification Of Epcsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Endothelial cells of the normal vasculature of normal tissues do not divide and form tight junctions that prevent free diffusion of ions and molecules into the tissue. In contrast, endothelial cells of a tumor vasculature contain 15-30% dividing cells and form a leaky endothelium, allowing free diffusion of ions and small molecules into the tumor.…”
Section: Introductionmentioning
confidence: 99%